A step-by-step guide to systematically identify all relevant animal studies - Leenaars, Marlies (Royal Society of Medicine Press, 2012)
Before starting a new animal experiment, thorough analysis of previously performed experiments is essential from a scientific as well as from an ethical point of view. The method that is most suitable to carry out such a thorough analysis of the literature is a systematic review (SR). An essential first step in an SR is to search and find all potentially relevant studies. It is important to include all available evidence in an SR to minimize bias and reduce hampered interpretation of experimental outcomes. Despite the recent development of search filters to find animal studies in PubMed and EMBASE, searching for all available animal studies remains a challenge. Available guidelines from the clinical field cannot be copied directly to the situation within animal research, and although there are plenty of books and courses on searching the literature, there is no compact guide available to search and find relevant animal studies. Therefore, in order to facilitate a structured, thorough and transparent search for animal studies (in both preclinical and fundamental science), an easy-to-use, step-by-step guide was prepared and optimized using feedback from scientists in the field of animal experimentation. The step-by-step guide will assist scientists in performing a comprehensive literature search and, consequently, improve the scientific quality of the resulting review and prevent unnecessary animal use in the future.